Pengaruh Model Problem Based Learning Berbantuan Media Interaktif Canva terhadap Hasil Belajar Informatika Siswa SMA - Julianti, Delia; Delianti, Vera Irma (Lembaga Yasin AlSys, 2025)
The low level of understanding among Grade X students regarding Informatics concepts—evidenced by the failure to meet the Target Criteria for Learning Objectives Achievement (KKTP)—serves as the background for this study. The teacher-centered learning approach has resulted in low student engagement, which negatively impacts learning outcomes. This study aims to analyze the effect of implementing the Problem Based Learning (PBL) model integrated with the interactive media Canva on students' learning outcomes in Informatics. A quantitative approach was used with a quasi-experimental design of the Nonequivalent Control Group Design type. The research was conducted at SMAN 2 Padang Panjang, involving 72 Grade X students. One class received treatment using PBL supported by Canva, while the control class applied PBL without media. The research instrument was a multiple-choice test used to measure learning outcomes. Data were analyzed using a t-test to assess differences in learning improvement between the two groups. The results showed that the group using PBL with Canva improved their average score from 53.50 to 86.14, while the group without media increased from 58.22 to 77.97. The study concludes that integrating the PBL model with interactive Canva media significantly enhances students’ conceptual understanding and learning outcomes in Informatics. The findings imply the importance of incorporating digital media to support active learning models and improve instructional effectiveness at the secondary school level.